Efektivitas Penggunaan Media Infografis Dalam Meningkatkan Keterampilan Menulis Karangan Argumentatif Pada Siswa Kelas XI SMK Negeri Sragi Kecamatan Sragi Kab. Pekalongan Jawa Tengah - Tiara Ayudhya Putri (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
The purpose of this study is to investigate whether the use of infographic media can enhance the argumentative writing skills of eleventh-grade students at SMK Negeri Sragi, located in the Sragi District of Pekalongan Regency, Central Java. Argumentative writing is a critical academic skill that enables students to express opinions clearly, logically, and persuasively. However, many students struggle with organizing their ideas, building coherent arguments, and presenting supporting evidence effectively. To address this issue, the research employs a quantitative descriptive method with a pre-test and post-test design. A total of 30 students from grade XI were randomly selected as research participants. Infographics were introduced as an instructional medium to assist students in better understanding the structure of argumentative texts, including thesis statements, supporting arguments, counterarguments, and conclusions. The visual nature of infographics was expected to improve students’ ability to grasp and organize key components of argumentative writing. The results of data analysis indicate a significant improvement in students’ writing performance after the implementation of infographic-based instruction. Students demonstrated enhanced clarity, coherence, and persuasiveness in their arguments. Furthermore, the use of infographics increased student motivation and confidence in expressing opinions through writing. This research concludes that infographic media is an effective tool for improving argumentative writing skills among vocational high school students. It is recommended that educators incorporate visual learning tools such as infographics to support writing instruction. The findings are expected to contribute to the development of more engaging and innovative teaching strategies that promote critical thinking and communication skills in the classroom.